THE USE OF LYRICSTRAINING WEBSITE TO IMPROVE STUDENT’S LISTENING COMPREHENSION IN SENIOR HIGH SCHOOL - Ozi Azhari; Aryuliva Adnan (Universitas Negeri Padang, 2018)
Among the four language skills, listening is one of the language skills that must be mastered and is important to be taught by a teacher to students in learning English. In line with the importance of listening, a teacher must be creative to make listening learning more enjoyable. One of them is by applying interesting and appropriate technique and media in listening learning. So, students are interested and motivated to learn it. In this paper, the author discusses how to improve student listening comprehension through the LyricsTraining.com online site. This website uses music video as a more interesting learning tool to practice English language skills, especially Listening. LyricsTraining provides authentic, complete, new and interesting listening learning materials from various types of music videos on YouTube. In addition to students, the teacher can also make his own material by creating an account on the Lyricstraining.com site. Through writing this paper the authors hope to introduce listening learning media that can motivate students and apply English in their daily lives.